(untitled) (GEON Journal (Management, Organizations and Business), 2021)
Problem: entrepreneurship has had a boom over the years, given its importance for the economic and social development of a region; however, in the context of research, knowledge about the entrepreneurial action of women is scarce. Objectives: in this sense, the article focuses on presenting the criteria for the success of women’s entrepreneurship and their business units, located in commune 1 of the city of Villavicencio, from an accounting and economic perspective. Materials and methods: the methodology that guides the development of the study is qualitative, with the application of a semi-structured interview to collect the information obtained from the participating businesswomen, which constitute a unit of analysis. Results: for the analysis of qualitative information, the categories and subcategories are established, in accordance with the success criteria and as a support for the social and economic characterization of women and their business units. Discussion: these observations account for different outstanding situations in their business work. Conclusion: the entrepreneurial exercise of women is a substantial contribution to their lives, their families and society in general. Contribution/originality: this research contributes to unveil female business empowerment, within a series of reports that only see women as victims.